Проблемні питання в дослідженні радіаційної обстановки під час реалізації проектів на об’єкті "Укриття" та шляхи вирішення їх - Єгоров, В.В.; Павловський, Л.І.; Стоянов, О.І.; Федорченко, Д.В. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
Розглянуто проблемні питання відповідності перед проектних вимірювань потужності дози до реальних показників при здійснені проектів на об’єкті «Укриття». Запропоновано комплексно-методичний підхід для підвищення точності досліджень радіаційної обстановки на радіаційно-небезпечних об’єктах із сильною анізотропією гамма-випромінювання. Рассмотрены проблемные вопросы соответствия предпроектных измерений мощности дозы и реальных значений при осуществлении проектов на объекте «Укрытие». Предложен комплексно-методический подход для повышения точности исследования радиационной обстановки на радиационно-опасных объектах с сильной анизотропией гамма-излучения. The problems of the correspondence of pre-project measurements of dose rate and real values in the implementation of projects at the object "Ukryttya" are considered. The inadequacy of the dose rate data obtained during the study leads to additional doses of personnel and an increase in the cost of the project. A complex-methodical approach is proposed to improve the accuracy of the investigation of the radiological conditions at radiation-hazardous objects with strong gamma-ray anisotropy. The use of a suite of radiometric equipment and a set of methods for measuring the energy characteristics and intensity of the angular distribution of gamma radiation, as well as the use of a spatial model for modeling the change in radiation conditions during operation, will significantly reduce the difference in radiation conditions. This approach has not been used previously.